2010
DOI: 10.1111/j.1365-3040.2010.02211.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light on cyanide‐resistant respiration and alternative oxidase function in Arabidopsis seedlings

Abstract: Mitochondrial alternative oxidase (AOX), the unique respiratory terminal oxidase in plants, catalyzes the energy wasteful cyanide (CN)-resistant respiration and plays a role in optimizing photosynthesis. Although it has been demonstrated that leaf AOX is upregulated after illumination, the in vivo mechanism of AOX upregulation by light and its physiological significance are still unknown. In this report, red light and blue light-induced AOX (especially AOX1a) expressions were characterized. Phytochromes, photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 53 publications
7
84
0
Order By: Relevance
“…Such studies comparing the Arabidopsis wild type and aox1a plants have, in general, demonstrated modest perturbations of A n and/or Chl fluorescence parameters (Zhang et al, 2010;Florez-Sarasa et al, 2011;Yoshida et al, 2011b;Gandin et al, 2012;Vishwakarma et al, 2014). The results are consistent with there being little if any perturbation of respiration rate in the Arabidopsis aox1a plants (see the introduction), albeit only R D rates (not R L ) have been reported thus far.…”
Section: Does Aox Have a General Role In Optimizing Photosynthetic Pesupporting
confidence: 69%
See 1 more Smart Citation
“…Such studies comparing the Arabidopsis wild type and aox1a plants have, in general, demonstrated modest perturbations of A n and/or Chl fluorescence parameters (Zhang et al, 2010;Florez-Sarasa et al, 2011;Yoshida et al, 2011b;Gandin et al, 2012;Vishwakarma et al, 2014). The results are consistent with there being little if any perturbation of respiration rate in the Arabidopsis aox1a plants (see the introduction), albeit only R D rates (not R L ) have been reported thus far.…”
Section: Does Aox Have a General Role In Optimizing Photosynthetic Pesupporting
confidence: 69%
“…In recent years, the potential importance of specifically AOX respiration during photosynthesis has been examined using the Arabidopsis aox1a plants (Giraud et al, 2008;Strodtkötter et al, 2009;Zhang et al, 2010;Florez-Sarasa et al, 2011;Yoshida et al, 2011aYoshida et al, , 2011b. In general, these studies reported small perturbations of photosynthesis in standard-grown aox1a plants, including slightly lower rates of CO 2 uptake or O 2 release (Gandin et al, 2012;Vishwakarma et al, 2014), slightly higher rates of cyclic electron transport (CET; Yoshida et al, 2011b), and slightly increased susceptibility to photoinhibition after a high light treatment (FlorezSarasa et al, 2011).…”
mentioning
confidence: 99%
“…Among these AOX genes, AOX1a is the most intensively studied and is the most responsive to stress. In Arabidopsis, this gene is induced by most abiotic stresses including drought, chilling, high salt, high light, and limitation of nitrogen [4,6,23,40,41]. Furthermore, using transgenic A. thaliana with varying expression levels of AOX1a, it demonstrated that the induction of AOX1a under abiotic stresses is actually associated with the tolerance of plants.…”
Section: Expression Of Aox Genes Under Abiotic Stressesmentioning
confidence: 99%
“…Abiotic stresses such as drought (Bartoli et al, 2005), high salt (Costa et al, 2007;Feng et al, 2010a), low temperature (Vanlerberghe and McIntosh, 1992;Popov et al, 2011;Wang et al, 2011), and wounding (Hiser and McIntosh, 1990) are known to stimulate the activity of alternative respiratory pathways or at least increase AOX transcripts and/or protein levels. Phytochrome, phototropin, and cryptochrome photoreceptors have been shown to mediate the light-responsiveness of the AOX1a gene in Arabidopsis (Arabidopsis thaliana) seedlings, and aox1a mutants showed increased photobleaching damage under high light conditions (Zhang et al, 2010). Several studies have indicated that AOX may also function in resistance to biotic stress such as infection by pathogens.…”
mentioning
confidence: 99%